The Relationship Between Big Five Personality Traits and Self-Regulated Learning in the Workplace: The Mediating Role of Goal Orientation - Haris Ali Akbar; Endang Parahyanti (Publikasi Indonesia, 2026)
Shifts in work dynamics and the growing demand for self-directed learning in the workplace have made self-regulated learning increasingly important in organizational settings. However, research on internal factors that predict employees’ self-regulated learning remains limited, particularly with respect to the psychological mechanisms linking personality to self-regulated learning. This study aims to examine the relationship between three Big Five personality traits (conscientiousness, openness, and neuroticism) and self-regulated learning in the workplace, and to evaluate the mediating role of goal orientation (learning goal orientation and performance-avoid goal orientation) in these relationships. Drawing on the Dual Processing Self-Regulation Model and Five Factor Theory, this study examined the relationship between three Big Five personality traits (conscientiousness, openness, and neuroticism) and self-regulated learning in the workplace, and evaluated goal orientation (learning goal orientation and performance-avoid goal orientation) as a mediator. Using a cross-sectional correlational design, data were collected from 139 professionals, most of whom resided in Indonesia. Results indicated that conscientiousness and openness were positively correlated with self-regulated learning, whereas neuroticism was negatively correlated. Mediation analyses showed that learning goal orientation partially mediated the relationships between conscientiousness and openness and self-regulated learning, while performance-avoid goal orientation partially mediated the relationship between neuroticism and self-regulated learning. These findings suggest that individual differences in employees’ self-regulated learning are related to both personality and goal orientation, and highlight goal orientation as a motivational pathway that helps explain, in part, the relationship between personality and self-regulated learning in the workplace.